Replacement of Sodium Bicarbonate and Micronutrients in Kosaric Medium With Banana Leaf Ash Extract for Culture of Spirulina Platensis (Annals of Bangladesh Agriculture, 2020)
Spirulina platensis is one of the most promising microalgae for culture due to its high nutritional values. The main constraint to its production is the high cost of culture media. Therefore, an experiment was conducted to evaluate the growth performance of S. platensis with the aim of replacing sodium bicarbonate (NaHCO3) and mineral nutrients in Kosaric medium (KM) with banana leaf ash extract. KM was used as control medium in treatment T1. In treatments T2 to T5, 50% of NaHCO3 in KM was replaced with banana leaf ash extract (BLAE). In addition, micronutrients in KM were reduced to 75%, 50% and 25% in treatments T3 to T5, respectively. The values of different physical and chemical parameters (temperature, pH, dissolved oxygen and light intensity) of the culture media were within the suitable range for S. platensis culture. Optical density in treatments T2 and T3 were similar to that was in treatment T1. Maximum cell dry weight (0.65 gL-1) was observed in treatment T1 and it was similar to the treatments T2 and T3 where 50% of NaHCO3 in KM was replaced with banana leaf ash extract with 100% and 75% micronutrients supply, respectively. The similar trend was found in chlorophyll a content. It was evident that 50% of NaHCO3 in KM can be replaced with BLAE for the culture of S. platensis, in addition micronutrients in KM can be reduced to 75%.Ann. Bangladesh Agric. (2019) 23(1) : 37-47